Contradictions and Limitations of Final Offer Selection: The Manitoba Experience. A Comment. - Grant, Hugh (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1990)
Contradictions and Limitations of Final Offer Selection : The Manitoba Experience. A Comment